Sosialisasi Observasional Pentingnya Kelestarian Mangrove di Areal Sempadan Pantai Kepada para Siswa Sekolah Dasar di Desa Cemarajaya Kecamatan Cibuaya Kabupaten Karawang - Medi Nopiana; Muhammad Nasim Harahap; Muis (Randang Tana - Jurnal Pengabdian Masyarakat, 2022)
Severe coastal erosion in some coastal areas of Karawang Regency, one of which is in Cemarajaya Village, Cibuaya Subdistrict, has impacted the community's socio-economic activities. Efforts to prevent coastal erosion can be carried out, among others, through coastal rehabilitation by planting mangroves. However, the village community's knowledge, understanding, and perception in preserving the mangrove ecosystem are still low. Therefore, it is necessary to implement socialization activities on preserving mangrove ecosystems, especially in coastal boundary areas, to prevent coastal erosion. The method of implementing this activity uses the observational socialization method. The community service activity results benefit the village government, educational institutions (schools), and the local community.